Answer:
He would need to purchase 8 ticket books. 8*24=192
Step-by-step explanation:
171/24=7.125 so he would need 8 books
Answer:
a) 301.59 cubic centimeters
b) 235.87 square centimeters
Step-by-step explanation:
a)
Volume of ice cream cone is volume of hemisphere PLUS volume of cone.
Volume of Hemisphere = ![\frac{\frac{4}{3}\pi r^3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B4%7D%7B3%7D%5Cpi%20r%5E3%7D%7B2%7D)
radius is given as 4, so,
Volume of Hemisphere = ![\frac{\frac{4}{3}\pi r^3}{2}\\=\frac{\frac{4}{3}\pi (4)^3}{2}\\=134.04](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B4%7D%7B3%7D%5Cpi%20r%5E3%7D%7B2%7D%5C%5C%3D%5Cfrac%7B%5Cfrac%7B4%7D%7B3%7D%5Cpi%20%284%29%5E3%7D%7B2%7D%5C%5C%3D134.04)
Now, Volume of Cone = ![\frac{1}{3}\pi r^2 h](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%5Cpi%20r%5E2%20h)
Where radius is 4 and height is 10, so,
Volume of Cone = ![\frac{1}{3}\pi r^2 h\\=\frac{1}{3}\pi (4)^2 (10)\\=167.55](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%5Cpi%20r%5E2%20h%5C%5C%3D%5Cfrac%7B1%7D%7B3%7D%5Cpi%20%284%29%5E2%20%2810%29%5C%5C%3D167.55)
Volume of Ice Cream Cone = 134.04 + 167.55 = 301.59 cubic centimeters
b)
Surface area of ice cream cone is surface area of hemisphere PLUS surface area of cone.
Surface Area of Hemisphere = ![2\pi r^2\\=2\pi (4)^2\\=100.53](https://tex.z-dn.net/?f=2%5Cpi%20r%5E2%5C%5C%3D2%5Cpi%20%284%29%5E2%5C%5C%3D100.53)
Surface Area of Cone = ![\pi r^2+\pi rl](https://tex.z-dn.net/?f=%5Cpi%20r%5E2%2B%5Cpi%20rl)
We dont need to use the first part,
since it is "inside". We need to find l, slant height, by using pythagorean theorem on a triangle we can make (bottom right).
4^2 + 10^ 2 = l^2
16 + 100 = l^2
116 = l^2
l = 10.77
Now to find the surface area of cone = ![\pi rl\\=\pi (4)(10.77)\\=135.34](https://tex.z-dn.net/?f=%5Cpi%20rl%5C%5C%3D%5Cpi%20%284%29%2810.77%29%5C%5C%3D135.34)
Surface area of ice cream cone = 100.53 + 135.34 = 235.87 square centimeters
The answer is 96*5 =480 so nancy will call 480 people in a 5 day workweek
Answer:
y = 3
x = 2
Step-by-step explanation:
-5x + 4y = 2
9x - 4y = 6
Sum both eq.
-5x + 9x = 4x
+4y - 4y = 0
2 + 6 = 8
then:
4x + 0 = 8
4x = 8
x = 8/4
x = 2
from the first eq.
-5x + 4y = 2
-5*2 + 4y = 2
-10 + 4y = 2
4y = 2 + 10
4y = 12
y = 12/4
y = 3
Check:
from the second eq.
9x - 4y = 6
9*2 - 4*3 = 6
18 - 12 = 6
They are equivalent. combine like terms on the first one and 9x-4x+25 can be simplified to 5x+25.